2016
DOI: 10.5194/acp-16-13309-2016
|View full text |Cite
|
Sign up to set email alerts
|

The climatology of planetary boundary layer height in China derived from radiosonde and reanalysis data

Abstract: Abstract. The important roles of the planetary boundary layer (PBL) in climate, weather and air quality have long been recognized, but little is known about the PBL climatology in China. Using the fine-resolution sounding observations made across China and reanalysis data, we conducted a comprehensive investigation of the PBL in China from January 2011 to July 2015. The boundary layer height (BLH) is found to be generally higher in spring and summer than that in fall and winter. The comparison of seasonally av… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
323
1
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 450 publications
(350 citation statements)
references
References 44 publications
24
323
1
2
Order By: Relevance
“…The boundary layer height was set as constant to 1000 m in the model due to the lack of measurements. This was similar to model setups in Lu et al (2013) and field measurement results in Guo et al (2016).…”
Section: Box Modelmentioning
confidence: 88%
“…The boundary layer height was set as constant to 1000 m in the model due to the lack of measurements. This was similar to model setups in Lu et al (2013) and field measurement results in Guo et al (2016).…”
Section: Box Modelmentioning
confidence: 88%
“…1c in Zhuang et al, 2013b). Thus, the higher AAC values in winter than in summer might result from the higher aerosol emissions, lower boundary height (Guo et al, 2016b) and less rainfall. However, possibly due to the impacts of hygroscopic growth of aerosol caused by higher RH in summer and dust aerosol in spring (Zhuang et al, 2014a), SC is considerably large in these two seasons (Fig.…”
Section: Temporal Variations Of the Aerosol Optical Propertiesmentioning
confidence: 99%
“…The PBLHs are extracted from the European Centre for Medium-Range Weather Forecasts (ECMWF) interim reanalysis (ERA-Interim; Dee et al, 2011), with a horizontal resolution of 0.125 • × 0.125 • and 3 h temporal resolution. Guo et al (2016b) have investigated the PBLH in China from January 2011 to July 2015 using both the fine-resolution sounding observations and ECMWF reanalysis data. It was found that the seasonally averaged PBLHs derived from reanalysis are generally in good agreement with those of observations in Beijing.…”
Section: Meteorological Datamentioning
confidence: 99%